Efficient mineralization of TBBPA via an integrated photocatalytic reduction/oxidation process mediated by MoS2/SnIn4S8 photocatalyst. (December 2021) - Weng, Rengui; Tian, Feng; Yu, Zhendong; Ma, Jiachen; Lv, Yuancai; Xi, Beidou
Abstract: Currently, Tetrabromobisphenol A (TBBPA) has been regarded as an emerging organic pollutant and efficient TBBPA elimination technology has been attracting increasing attention. In this work, a novel photocatalyst, MoS2 /SnIn4 S8, was synthesized through hydrothermal method by introducing few-layer MoS2 nanosheets and then employed to establish an integrated photocatalytic reduction/oxidation system for the remediation of TBBPA under visible light. The characterization results demonstrated that the few-layer MoS2 nanosheets were well combined with SnIn4 S8 and significantly lowered the recombination rate of the photo-induced electron and holes, leading to outstanding photocatalytic performance of MoS2 /SnIn4 S8 composite. Besides, the MoS2 /SnIn4 S8 composite also exhibited excellent reusability (over 10 runs) and stability. The TBBPA degradation experiments showed that the integrated photocatalytic reduction/oxidation system was able to completely degrade TBBPA and mineralize its byproducts (60.2 ± 2.9%). In the photocatalytic reduction, due to the cleavage of C–Br bonds by photo-induced electrons, TBBPA underwent stepwise debromination and finally transferred into BPA in 6 h. In the following photocatalytic oxidation, under the attack of reactive oxygen species ( 1 O2, h +, OH and O2 − ), BPA was first decomposed into aromatic products (such as phenol, benzoic acid, p -hydroxybenzyl alcohol and so on) via C–C bond cracking and hydroxylation, and then further oxidized into organic acids like maleic acid and muconic acid through ring-opening, and finally mineralized into CO2 and H2 O. What was noteworthy was that the final effluent from the photocatalytic reduction/oxidation system showed no toxicity to the luminescent bacteria. Graphical abstract: Image 1 Highlights: Structure and photocatalytic performance of MoS2 /SnIn4 S8 were studied. TBBPA could be fully degraded during photocatalytic reduction/oxidation. Stepwise debromination of TBBPA occurred during photocatalytic reduction. O2 − and h + were the main species during photocatalytic oxidation of BPA. The final effluent from the system were proved to nontoxic.